PENERAPAN MILIEU TEACHING DALAM MENINGKATKAN KEMAMPUAN BAHASA EKSPRESIF PADA ANAK YANG MENGALAMI KETERLAMBATAN BAHASA - Merdiasi, Danella; Tiatri, Sri; Dewi, Fransisca I.R. (Universitas Islam Negeri Alauddin Makassar, 2017)
This study aims to determine the implementation of milieu teaching in improving the ability of expressive language in children who experience language delays. One of the early language interventions used was milieu teaching. Milieu teaching is a naturalistic intervention approach that uses conversational-based strategies to improve language and communication skills in children. Participants in this study amounted to 1 child of a 4-year-old male who experienced language delays and is currently studying in Kindergarten. This research is an experimental research with research design that is single subject design. In this research design, there will be three sessions, namely baseline 1, intervention phase, and baseline 2 stages in order to find out whether or not there is an increase in each session. Data analysis techniques used are visual data analysis techniques based on the results of observation data. Based on the calculation, it is known that there is an improvement of expressive language in children who experience language delay through the application of milieu teaching.